Canva application training for social media promotion content for tourism awareness groups in Pela Village, Kutai Kartanegara Regency - Ramadhan S. Pernyata; Royke Vincentius F.; Ditha Nizaora (Universitas Muhammadiyah Magelang, 2022)
As one of the leading tourist destinations in East Kalimantan, the promotion aspect is still an emerging review for Pela Village tourism managers. The purpose of this program is to provide design skills using the Canva application that can be used for content purposes in the form of banners and posters. Canva is a graphic design application that bridges its users so that they can easily design types of creative content and publications online. The program method used is lectures, practical examples, presentations and demonstrations. The result of this program is an increase in understanding and ability to process visual assets and textual information into an aesthetic work in the form of promotional posters and banners for Pela Tourism Village. This can be a provision for Pela Village Pokdarwis in making other tourism promotion content that is creative and easy to apply.